1998
DOI: 10.1002/(sici)1521-4141(199809)28:09<2872::aid-immu2872>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Impaired MHC class I (H-2Dd)-mediated protection against Ly-49A+ NK cells after amino acid substitutions in the antigen binding cleft

Abstract: The MHC class I molecule H-2Dd (Dd) acts as a ligand for the inhibitory NK cell receptor Ly-49A. We have constructed altered Dd molecules by site-directed mutagenesis, replacing residues with the corresponding amino acids from the Db molecule, which fails to inhibit via Ly-49A. Mutations at positions 73 and 156 (DdS73WD156Y) impaired the protective effect of the Dd molecule, as evaluated by testing lymphoma cells transfected with the mutant gene for sensitivity to killing by Ly-49A+ NK cells in vitro and rejec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…The important areas include ␤-sheet regions that form the bottom of ␣1/␣2 domain rather than ␣ helices of ␣1/␣2 domains, which form the functional binding site for Ly49A by the crystal structure data and our more recent mutagenesis data (28). Furthermore, other investigators have reported that mutations in residues that affect the peptide binding cleft may also affect Ly49A interaction (29,30). Therefore, the contribution of H-2D d residues that do not directly contact Ly49A requires further investigation.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…The important areas include ␤-sheet regions that form the bottom of ␣1/␣2 domain rather than ␣ helices of ␣1/␣2 domains, which form the functional binding site for Ly49A by the crystal structure data and our more recent mutagenesis data (28). Furthermore, other investigators have reported that mutations in residues that affect the peptide binding cleft may also affect Ly49A interaction (29,30). Therefore, the contribution of H-2D d residues that do not directly contact Ly49A requires further investigation.…”
supporting
confidence: 75%
“…Recently, Waldenström et al reported that simultaneous introduction of S73W and D156Y mutation into H-2D d partially impairs H-2D d -mediated protection against killing by Ly49A ϩ NK cells (29). These substitutions putatively introduce a ridge inside the peptide binding groove that is found in H-2D b .…”
Section: Effect Of Mutation In Conserved Residues In ␣1 Domain Of H-2mentioning
confidence: 52%
See 2 more Smart Citations
“…Site 1 had a relatively small binding area covering the glycosylation site at residue N176, while site 2 had a large binding area spanning the ␣ 1 , ␣ 2 , ␣ 3 , and ␤ 2 -microglobulin (␤ 2 m) domains of H-2D d . Mutational studies of H-2D d have suggested that site 2 is the predominant site of the Ly-49A-H-2D d interaction (22,(32)(33)(34). The Ly-49C-MHC class I interaction has not been studied as extensively.…”
mentioning
confidence: 99%